Death and the Times: Depictions of War Deaths in the United States and Israel From Vietnam and the Six-Day War to Iraq and Lebanon - Lachmann, Richard (2012)
Why has support for casualties in foreign wars declined in the United States since Vietnam? We compare The New York Times’ very different depictions of war deaths in the Vietnam and Iraq wars. Then we offer an explanation for why there has been this fundamental transformation in the ways in which American war dead are regarded and valued. We find that the change is in retrospective interpretations of the war and in memorials to the Vietnam dead after that war ended rather than in public evaluations of the geopolitical interests of the U.S. or prospects for victory in either Vietnam or Iraq. We trace the deepening personalization of war dead to specific political and cultural events within the United States rather than positing a general change in Western attitudes toward death and war. We conclude by speculating on the implications of that change for future wars and propose a research agenda to extend our findings to other countries that have fought wars in recent decades.